Manajemen Strategik dalam Meningkatkan Daya Saing Perusahaan di Era Digital - Dewi , Putri Cantika; Srisusilawati, Popon (Economics and Digital Business Review, 2025)
This research analyzes the application of strategic management to improve the competitiveness of companies in the digital era. Rapid digital transformation changes business competition, forcing companies to adjust strategies to technological developments and market needs. The method used is a qualitative literature study, reviewing related journals, books, and articles. The results show that digital strategies, such as the use of big data, artificial intelligence, and e-commerce, can strengthen a company's competitiveness. The conclusion of this study is that effective strategic management in the digital era requires flexibility in responding to technology as well as the ability to innovate and adapt to customer needs.